2018
DOI: 10.1038/s41598-018-26691-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Nonsusceptible Klebsiella pneumoniae in Taiwan: Dissemination and Increasing Resistance of Carbapenemase Producers During 2012–2015

Abstract: Before 2011, the prevalence rates of carbapenemase-producing Klebsiella pneumoniae (CPKP) among carbapenem nonsusceptible K. pneumoniae (CnSKP) isolates were below 10% in Taiwan. The study presents the dissemination and increased antimicrobial resistance of CPKP from January 2012 to August 2015, as shown by Taiwanese multicenter surveillance. Isolates with minimum inhibitory concentrations (MICs) of >1 μg/mL for imipenem or meropenem were collected, screened for various carbapenemase genes by PCR, and tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
6
27
0
2
Order By: Relevance
“…Furthermore, it is noteworthy that the prevalence rates of CPE [36.4%; mostly related to various bla KPC (75.9%), followed by bla OXA-48 -like (8.8%), bla V IM-1 (7.9%), and bla IMP-8 (5.7%), etc] among the studied CR- K. pneumoniae isolates (approximately 99% were non-susceptible to imipenem, and 85.8% were collected from medical centers) were estimated to have 1.5-fold increase from 2012 through 2015. Most significantly, an increasing trend was observed in the middle-western part of Taiwan ( Chiu et al, 2018 ). Data regarding important CRE studies in Taiwan and other countries are shown in Table 1 .…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is noteworthy that the prevalence rates of CPE [36.4%; mostly related to various bla KPC (75.9%), followed by bla OXA-48 -like (8.8%), bla V IM-1 (7.9%), and bla IMP-8 (5.7%), etc] among the studied CR- K. pneumoniae isolates (approximately 99% were non-susceptible to imipenem, and 85.8% were collected from medical centers) were estimated to have 1.5-fold increase from 2012 through 2015. Most significantly, an increasing trend was observed in the middle-western part of Taiwan ( Chiu et al, 2018 ). Data regarding important CRE studies in Taiwan and other countries are shown in Table 1 .…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 99%
“…There were big variations in the rates of CPE among clinical CRE isolates in Taiwan as compared to those from other countries ( Lorenzoni et al, 2017 ; Woodford et al, 2017 ; Laolerd et al, 2018 ). It is notable that persistently high KPC-2 rates (73.9% in 2012, and 61.1% in 2015) and emergence of KPC-17 as well as KPC-34 since 2014 were observed ( Chiu et al, 2018 ). As the K. pneumoniae of ST11 clone accounted for 86.9% of overall CP- K. pneumoniae isolates ( Chiu et al, 2018 ), heightened infection control maneuvers are absolutely warranted for Taiwanese medical centers.…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 99%
“…T he endemic spread of carbapenemase-producing Klebsiella pneumoniae in Taiwan has become problematic (1). Besides the predominance of Klebsiella pneumoniae carbapenemase (KPC)-2, oxacillinase (OXA)-48 emerged at the end of 2013 (2) and has become the second most prevalent (1).…”
mentioning
confidence: 99%
“…T he endemic spread of carbapenemase-producing Klebsiella pneumoniae in Taiwan has become problematic (1). Besides the predominance of Klebsiella pneumoniae carbapenemase (KPC)-2, oxacillinase (OXA)-48 emerged at the end of 2013 (2) and has become the second most prevalent (1). Previously, we demonstrated that KPC-2 and OXA-48 accounted for 36.2% and 12.6% of carbapenem-resistant K. pneumoniae isolates, respectively, and most of them belonged to sequence type (ST) 11 (3).…”
mentioning
confidence: 99%
“…The production of AmpC or ESBLs combined with loss or decreased expression of out membrane protein (19,20). In addition, studies have found that the susceptibility of Escherichia coli and Enterobacter cloacae to carbapenem can be increased when the AcrAB-TolC e ux pump is inhibited (21,22).…”
Section: Discussionmentioning
confidence: 99%